Consumption grants: water analysis in the Municipality of Unaí – MG (Research, Society and Development, 2021)
Brazil is a privileged country in terms of total water availability; however, its distribution is uneven in the territory, making the grant a necessary instrument for the management of water resources. Therefore, this study aims to analyze the current grants and confront them with the demand of the central pivots installed within the limit of the municipality of Unaí - MG. For the study, data from grants of federal dominance made available by ANA on the Regulation portal and data from grants at the State level made available by the Mineiro Institute of Water Management - IGAM were used. These data, manipulated through geoprocessing techniques to obtain the results. The municipality of Unaí has ​​a total of 420 surface abstraction granting concessions, 346 of which are federally owned and 74 of which are owned by the state of Minas Gerais, whose total flow granted is equivalent to 56.3 m³ s-1, being greater than the estimated demand for all central pivots in the municipality of Unaí concomitant with the cultivation of safrinha corn, flow around 35.1 m³ s-1. It should be noted that there may be some uncertainties in relation to the data, as it is known that there are still unregulated uses, limiting the calculation of the demand on the existing grants in the databases of the responsible agencies.